Methane production and nitrogen balance of dairy heifers grazing palisade grass cv. Marandu alone or with forage peanut - Berca, Andressa S. [UNESP]; Cardoso, Abmael da S. [UNESP]; Longhini, Vanessa Z. [UNESP]; Tedeschi, Luis O.; Boddey, Robert Michael; Berndt, Alexandre; Reis, Ricardo A. [UNESP]; Ruggieri, Ana Claudia [UNESP] (Oxford Univ Press Inc, 2019)
Livestock production systems are an essential agribusiness activity in Brazil, but a critical challenge of Brazilian farmers is to maintain the equilibrium of the ecosystem, using herbage resources efficiently with a minimum impact on the environment. Nitrogen (N) fertilization and the inclusion of forage legumes into tropical grass pastures are management strategies which increase the productivity and nutritive value of pastures and may also affect methane (CH 4) production by ruminants. The objective of this study was to examine the effects of either fertilizing palisade grass pastures with N or including the forage peanut (Arachis pintoi) into grass pastures on enteric CH4 emission, microbial protein production in the rumen via purine derivatives in the urine, and N balance. Twenty-one nonlactating crossbred dairy heifers were used in a completely randomized design with 3 treatments. The treatments consisted of pastures of palisade grass without N fertilization (control), fertilized with urea (fertilized), and palisade grass mixed with forage peanut (mixed). Seven animals (replications) were used to evaluate dry matter intake, digestibility, CH4 emission, urea, purine derivatives, and volume of urine, and N ingestion and excretion. Four paddocks (replications) were used to measure herbage mass; morphological, botanical, and chemical composition of herbage; and herbage allowance. The CH4 emissions were determined using the sulfur hexafluoride (SF6) tracer gas technique. The efficiency of N utilization (ENU) was calculated using the N balance data. Crude protein (CP) concentration of herbage increased with fertilization or legumes inclusion (P < 0.0001) while neutral detergent fiber (NDF) concentration decreased (P = 0.0355). The leaf allowance was higher in the fertilized treatment (P = 0.0294). Only uric acid excretion increased with N fertilization (P = 0.0204). The ENU was not affected by fertilized or mixed compared to control and averaged 55% (P = 0.8945). The enteric CH4 production was similar between treatments and averaged 129 g/d (P = 0.3989). We concluded that the changes in chemical composition of herbage provided by N fertilization or the inclusion of the legume showed no reduction in enteric CH4 emissions, but the ENU was more significant than previous studies with palisade grass, suggesting that different management strategies might alter the ENU under grazing conditions.
Keywords: Brachiaria grass; chemical composition; forage legumes; methane; mixed pastures; N excretion